Environmental Strategic Planning Rumah Sakit Persahabatan Menuju Green Hospital - Sunarto Sunarto (Universitas Negeri Jakarta, 2018)
The objective of this study is aim at finding out environmental strategic planning differences between what has been conducted by Persahabatan state hospital compared to theoretical prescription in building to be a green hospital. A descriptive-theoretical method has been applied for this purpose by implementing a content analysis which involved analyzing short/long term hospital strategic planning documents, 2015/2016. The results of this study revealed that environmental strategic management has been prepared in term of short (1 year) and long term (5 year plan), but it was not carried out in detail concern with budget and human resource allocation in accordance to their specialization in managing all green hospital concepts such as green building, the efficient use of electric energy, water, efficient use of papers, preventing air and water pollution, waste management, gardening, and building green corporate culture which emphasizing on environmental hospital performance. The later should be new concept in developing an environmental strategic planning as one of the contributions toward a green hospital which was neglected by some environmental strategic planning theories. Keywords: environmental strategic planning, waste management, green building, environmental corporation performance, green hospital.